Naruto,. Vol. 22., Comrades - Kishimoto, Masashi, 1974- (Shonen Jump manga., 2007)
Naruto sets off with Shikamaru to save Sasuke--who is trapped in the Darkness under the control of Orochimaru--leaving Neji to face Kidomaru alone.